Breastfeeding in infancy and mortality in middle and late adulthood: A prospective cohort study and meta‐analysis. (5th March 2023) - Wang, Xiaoyan; Yan, Mengsha; Zhang, Yanyu; Wang, Wenjie; Zhang, Weiwei; Luo, Junkai; Gan, Da; Yang, Haomin; Zhu, Shankuan; He, Wei
Abstract: Background: Breastfeeding in infancy is associated with a lower risk of mortality among children, but the impact on mortality in middle and late adulthood remains unknown. Objectives: To assess the association between breastfeeding in infancy and mortality in middle and late adulthood. Methods: We included 383, 627 participants aged 40–73 from the UK Biobank (2006–2010) and followed up until 2021. Hazard ratios (HRs) and 95% confidence intervals (CIs) for all‐cause and cause‐specific mortality according to breastfeeding in infancy were estimated with Cox proportional hazards regression models. We further did a meta‐analysis, including results from our present study and three other cohort studies (PROSPERO; number CRD42022348925). Results: During a total of 4732, 751 person‐years of follow‐up, 25, 581 deaths were identified. Breastfeeding in infancy was associated with lower risks of mortality in middle and late adulthood, with adjusted HRs (95% CIs) of 0.95 (0.93–0.98) for all‐cause mortality; 0.91 (0.87–0.96) for cardiovascular mortality and 0.94 (0.874–0.999) for respiratory mortality. Specifically, the association with mortality seemed to attenuate with age – stronger in middle‐aged adults than in older adults. A similar association between breastfeeding in infancy and all‐cause mortality was found in the meta‐analysis. Conclusion: Breastfeeding in infancy is associated with a lower risk of mortality – even decades later – in middle and late adulthood. Abstract :